Rheopathologic Consequence of Plasmodium vivax Rosette Formation. - Rou Zhang; Wenn-Chyau Lee; Yee-Ling Lau; Letusa Albrecht; Stefanie C P Lopes; Fabio T M Costa; Rossarin Suwanarusk; Francois Nosten; Brian M Cooke; Laurent Rénia; Bruce Russell (Public Library of Science (PLoS), 2016)
Malaria parasites dramatically alter the rheological properties of infected red blood cells. In the case of Plasmodium vivax, the parasite rapidly decreases the shear elastic modulus of the invaded RBC, enabling it to avoid splenic clearance. This study highlights correlation between rosette formation and altered membrane deformability of P. vivax-infected erythrocytes, where the rosette-forming infected erythrocytes are significantly more rigid than their non-rosetting counterparts. The adhesion of normocytes to the PvIRBC is strong (mean binding force of 440pN) resulting in stable rosette formation even under high physiological shear flow stress. Rosetting may contribute to the sequestration of PvIRBC schizonts in the host microvasculature or spleen.